ʿd dṿd hgdyl (1 Sam 20:41) – ʿd vṿr hgdṿl (1 Sam 19:22) - Goldstein, Ronnie (2021)
This study focuses on the difficult ending of 1 Sam 20:41 in the Masoretic text (MT): וַיִּבְכּוּ אִישׁ אֶת רֵעֵהוּ עַד דָּוִד הִגְדִּיל, rendered normally as “They wept together; David wept the longer.” Many have pointed out the peculiarity of this phrase, and different emendations were proposed, based mainly on the LXX. The present article suggests an emendation of 1 Sam 20:41, according to which the original text read here עד בור הגדול. The mention of the “Great Cistern” at the end of the previous story in the Book of Samuel (19:22), provides strong support for this suggestion. It is proposed that the mention of the “Great Cistern” in the original text intended to narrow the geographical gaps between the different stories about David and Saul.